The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3892/ijmm.2015.2343
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of regucalcin in kidney cell regulation: Involvement in renal failure (Review)

Abstract: Abstract. The kidneys play a physiologic role in the regulation of urine formation and nutrient reabsorption in the proximal tubule epithelial cells. Kidney development has been shown to be regulated through calcium (Ca 2+ ) signaling processes that are present through numerous steps of tubulogenesis and nephron induction during embryonic development of the kidneys. Ca 2+ -binding proteins, such as calbindin-D28k and regucalcin are important proteins that are commonly used as biomarkers in pronephric tubu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 73 publications
2
7
0
Order By: Relevance
“…Studies on in vivo RGN KO mice also revealed that RGN is related to the pathogenesis of diabetic nephropathy, nonalcoholic fatty liver disease, and hepatic steatosis [10,11]. We also found support for a physiological role of RGN in maintaining the function of kidney proximal tubular epithelial cells [12]. Diabetic nephropathy rats were shown to exhibit downregulated expression of RGN expression in kidney tissue and decreased amounts of RGN-present exosomes in urine [13].…”
supporting
confidence: 63%
“…Studies on in vivo RGN KO mice also revealed that RGN is related to the pathogenesis of diabetic nephropathy, nonalcoholic fatty liver disease, and hepatic steatosis [10,11]. We also found support for a physiological role of RGN in maintaining the function of kidney proximal tubular epithelial cells [12]. Diabetic nephropathy rats were shown to exhibit downregulated expression of RGN expression in kidney tissue and decreased amounts of RGN-present exosomes in urine [13].…”
supporting
confidence: 63%
“…Our data suggest that regucalcin overexpression causes G1 and G2/M phase cell cycle arrest in A498 cells. supporting the view that regucalcin plays a role in cell cycle arrest (22)(23)(24)(25)(26), and we demonstrate herein that thus is also the case in A498 cells.…”
Section: Discussionsupporting
confidence: 91%
“…The gene for regucalcin, which was discovered as a calcium-binding protein (15,16), is localized on the X chromosome (17)(18)(19). Regucalcin is expressed in various types of cells and tissues (20,21), and has been demonstrated to play multifunctional roles in the regulation of manifold cells (21)(22)(23)(24). Regucalcin has been shown to maintain calcium homeostasis, inhibit various signaling pathways involving various protein kinases and protein phosphatases, suppress cytosolic protein synthesis and nuclear DNA and RNA synthesis, and regulate nuclear gene expression in cells (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations